INCLUSIVE AND EQUITABLE LITERACY AND NUMERACY PRACTICES AT FOUNDATIONAL STAGE: GLOBAL AND COMPARATIVE PERSPECTIVE - Sthapak, Sonia; Sawlani, Rakhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is the output of the minor research project on FLN received by IITE Gujarat. It reviews the progression of Foundational Literacy, Language and Numeracy practices through content analysis of literature in the form of educational regulatory documents, policy briefs, dataset tracking the progress, need analysis, baseline-endline and assessment reports. The study underscores the significance and evolving role of foundational learning both now and in the future in preparing students for the complexities of the modern world offering an inclusive and equitable perspective on effective practices exploring how literacy, language, and numeracy strengthened through diverse educational initiatives and interventions. It also identifies the conditions for Foundational Literacy and Numeracy delivery at grassroot level for widespread adoption across three distinct categories of nations: developed, developing, and underdeveloped countries aiming to provide insights into their historical development and social contexts shaping the learning practices globally along with the role of the parent-community integration and involvement. The study underlines the accountability of Governments and education stakeholders worldwide specifically in high-income, middle-income, and low-income countries to endorse their major initiatives ensuring all children, including the most marginalized, develop necessary foundational skills in alignment with Sustainable Development Goals (SDG-4). While doing background briefing of different projects and programs at international and national level, few case-studies have been elaborated that emphasize the current state of FLN in various regions providing a broad perspective on foundational learning study across different educational contexts, often extending beyond traditional notions of basic education and existing systems.